The acceptance of organic farming technologies among small medium enterprise in Selangor / Farah Hanis Awang - Awang, Farah Hanis (Faculty of Business and Management, 2012)
Organic farming has taken its own place since years ago. As for Malaysia, it still can be considered as new. In this matter, many Small Medium Enterprises are reluctant to implement such technologies in expanding their business. There are many factors contributing towards these issues. Due to the lack of organic product in current market, the price of the organic products locally is sold at higher level compared to the other product. There are few factors that contribute to the acceptance of organic farming technologies. In the study conducted, there are three factors that have been studied in order to relate to the acceptance of the organic farming technologies. There are Performance Expectancy, Social Influence and Effort Expectancy. These three factors do have a relationship towards the acceptance of organic farming technologies. Performance expectancy is focusing more on the output generated from organic farming. This is more towards the sales generated by the SME’s if they implement such technologies. As for the Social Influence, the study is focusing more on the influence from the surroundings. There are influences from business partner, people who close and from the other entrepreneurs who in the same industry. For the Effort Expectancy, the study is focusing more on the level of complexity of implementing these technologies. The scope of the research is to study the factors that affect the acceptance of the organic farming among the SME’s in Selangor. Along with three factors that will lead to the acceptance of organic farming technologies which are Performance Expectancy, Social Influence and Effort Expectancy. It is found that the Performance Expectancy is the most significance variables that lead to the acceptance of organic farming technologies.